EXPLORING THE EVOLUTION AND ARTISTRY OF CALLIGRAPHY: A HISTORICAL ANALYSIS FROM THE 9TH TO 19TH CENTURY IN INDIAN HISTORY - Garima; Kumar, Narandra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the evolution and artistry of Indian calligraphy from the 9th to the 19th century through a thematic analysis of relevant literature. Tracing changes in scripts, styles, and cultural influences, the research delves into the dynamic interplay of artistic techniques and socio-cultural impact shaping Indian calligraphy over time. Drawing insights from diverse sources spanning from ancient Indian calligraphy from 9th to 19th century, the study illuminates the enduring legacy of calligraphy as a cultural artifact and artistic expression in Indian society. Through a nuanced examination of historical trends and cultural nuances, the research highlights the profound significance of Indian calligraphy as a testament to the artistic prowess and spiritual depth of its practitioners. The study concludes by emphasizing the importance of preserving and promoting India's calligraphic heritage for future generations, ensuring its continued appreciation and relevance in the ever-evolving cultural landscape.